Industrial localization and countries' specialization in the European Union: An empirical investigation - Astrid Krenz; Gerhard Rübel (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
The aim of this study is to empirically investigate the development of Industrial Localization and Countries' Specialization Patterns in the European Union, to explain the driving forces behind and to find out dynamic tendencies. We extend existing research work by using a broader data set, covering a longer period of time and by applying several econometric methods in order to explain Localization and Specialization. Explanatory variables are derived from Traditional Trade Theory, New Trade Theories and the New Economic Geography. Taking EU-KLEMS data for 14 European countries covering 20 industries over the period from 1970 to 2005 we compute both regional and locational Gini coefficients. There is a clear increase in Industrial Concentration but only a slight increase in Countries' Specialization in the EU evident over time. Especially, low technology or labor intensive industries experienced the highest increase in Industrial Concentration. New Trade Theory and New Economic Geography can explain both Industrial Concentration and Countries' Specialization in the EU best. As regards Countries' Specialization our results indicate that trade costs seem to have declined so much and European liberalization has proceeded so far that dispersion among countries occurs again. We show that it's important to consider multicollinearity problems of variables. Furthermore, we test for cointegration between our regression variables. For the EU, results of an error correction modeling framework show that imbalances in European Countries' Specialization are being set off at a rate of about 68 to 105 percent (according to the regression framework taken) within the next period. New Economic Geography is the best explanatory force within the error correction model. Adjustments rates for Sweden and Italy appear to be much lower than for the EU as a whole. These results might be valuable for understanding agglomeration processes in the EU. Also, as European Integration continues to progress, it is important to know how and how quickly countries will specialize and industries will agglomerate.
Keywords: C50; F14; F15; 330; New Economic Geography; Concentration; Specialization; European Integration; Cointegration; Produktionsstandort; Internationale Arbeitsteilung; Neue Ökonomische Geographie; Regionales Cluster; Wirtschaftsintegration; Kointegration; Schätzung; EU-Staaten